Two new species of the crangonid genus Metacrangon Zarenkov, 1965 (Crustacea: Decapoda: Caridea) from the Okinawa Trough, Japan - Komai, Tomoyuki; Chen, Chong; Watanabe, Hiromi Kayama (Zootaxa, 2018)
Two new species of the crangonid shrimp genus Metacrangon Zarenkov, 1965, are described and illustrated on the basis of materials collected from the Okinawa Trough, Ryukyu Islands, southern Japan, during diving operations of remotely operated vehicles (ROVs): M. ryukyu n. sp. from off Iheya Island, at depth of 986 m; and Metacrangon kaiko n. sp. from NE of Yonaguni Island, at depth of 2205 m. The two new species resemble members of the M. munita (Dana, 1852) species group, but are both characteristic in having setose dactyli on pereopods 4 and 5. Some minor differences in morphology and genetic analysis using partial sequences of the barcoding mitochondrial COI gene support the recognition of the two new species. Holotypes of the two new species were collected from hydrothermally influenced areas, representing a previously unknown habitat for species of Metacrangon.